2016
DOI: 10.1016/j.jpain.2016.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Altered Pain Perception and Fear-Learning Deficits in Subjects With Posttraumatic Stress Disorder

Abstract: There is growing evidence that fear learning abnormalities are involved in the development of posttraumatic stress disorder (PTSD) and chronic pain. More than 50% of PTSD patients suffer from chronic pain. This study aimed to examine the role of fear-learning deficits in the link between pain perception and PTSD. We included 19 subjects with PTSD and 21 age- and sex-matched healthy control subjects in a fear-conditioning experiment. The conditioned stimulus (CS) consisted of visual signs flashed upon a screen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 36 publications
1
16
0
Order By: Relevance
“…Heightened fear is a hallmark symptom of PTSD (Yehuda et al, 2015) and failure to utilize learned safety cues has been suggested as a biomarker of PTSD (Grillon and Morgan, 1999; Jenewein et al, 2016; Jovanovic et al, 2009; Jovanovic et al, 2012). What is striking about this phenomenon is that while individuals with PTSD understand the meaning of the safety cue, fear enhanced startle and other biomarkers of anxiety appear insensitive to regulation by the safety cue (Jovanovic et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Heightened fear is a hallmark symptom of PTSD (Yehuda et al, 2015) and failure to utilize learned safety cues has been suggested as a biomarker of PTSD (Grillon and Morgan, 1999; Jenewein et al, 2016; Jovanovic et al, 2009; Jovanovic et al, 2012). What is striking about this phenomenon is that while individuals with PTSD understand the meaning of the safety cue, fear enhanced startle and other biomarkers of anxiety appear insensitive to regulation by the safety cue (Jovanovic et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Further, when a safety cue is well learned, it can reduce fear in the presence of a danger cue, a learning phenomenon known as conditioned inhibition of fear (Kazama et al 2013). Overgeneralization of fearrelated cues and aberrant conditioned inhibition of fear are seen in individuals with post-traumatic stress disorder (PTSD) (Jovanovic et al 2012;Costanzo et al 2016;Jenewein et al 2016). Females are more likely to be diagnosed with PTSD than males (Kilpatrick et al 2013;Kessler et al 1995) and safety learning and discrimination are sensitive to hormonal birth control and trauma history in females compared with males (Gamwell et al 2015;Lornsdorf et al 2015).…”
mentioning
confidence: 99%
“…Stress is believed to be a physiological trigger for the descending pain regulation system, and pain can trigger an emotional response to stress ( Timmers et al 2019 ). Pain sensitivity may increase under chronic stress ( Jenewein et al, 2016 ). Both chronic stress and chronic pain are associated with certain brain networks, including the corticolimbic system and thalamus, and are both associated with increased anxiety (Vachon-Presseau et al 2018; Timmers et al 2019 ).…”
Section: Discussionmentioning
confidence: 99%